Study Of Self-Sovereign Identity Management System Incorporating Blockchain - Dixa Koradia (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Self-sovereignty can be defined as having control over the specifics of your own identity. ‘Self-sovereign identity (SSI)’ solutions aim to give users the ability to manage their identity without the need for central authorities or intermediaries. One of the key technologies commonly used to implement SSI is decentralized ledger technology, such as blockchain. It is immutable and distributed ledger capabilities provide a robust foundation for identity verification, authentication, and data sharing. Through the use of cryptographic mechanisms and digital signatures, users can maintain ownership of their identity attributes and selectively disclose information as needed. The term ‘identity management system (IDMS)’ describes the procedure for identifying and authorizing users or persons to access corporate systems and services. Single points of failure cannot be reduced by conventional identity management and authentication systems because they rely so largely on a reliable central authority. In recent years, the field of IDMS has paid a lot of attention to Blockchain (BC) technology, which functions as a decentralized and distributed public ledger in a peer-to-peer (P2P) network. Overall, the survey provides valuable insights into the implementation of a blockchain-based SSI system. It contributes to the growing body of knowledge in the field of identity management and showcases the promising potential of blockchain technology in redefining the way we manage digital identities.